Ketamine and Peripheral Inflammation. (10th April 2013) - De, Marc; Loix, Sebastien; Lavand'homme, Patricia
Summary The old anesthetic ketamine has demonstrated interactions with the inflammatory response. This review intends to qualify the nature and the mechanism underlying this interaction. For this purpose, preclinical data will be presented starting with the initial works, and then, the probable mechanisms will be discussed. A summary of the most relevant clinical data will be presented. In conclusion, ketamine appears as a unique "homeostatic regulator" of the acute inflammatory reaction and the stress‐induced immune disturbances. This is of some interest at a moment when the short‐ and long‐term deleterious consequences of inadequate inflammatory reactions are increasingly reported. Large‐scale studies showing improved patient's outcome are, however, required before to definitively assert the clinical reality of this positive effect.